Penerapan Model Pembelajaran Berbasis Masyarakat sebagai Upaya Meningkatkan Mutu Pendidikan di Sekolah Dasar - Ulis Sikhah (Perkumpulan Kualitama Edukatika Indonesia, 2022)
This study aims to find out about improving the quality of education through the application of community-based learning models. The focus of research is on policies, programs, strategies and disciplines for school principals, teachers, archivists and school committees. A qualitative naturalistic approach was used in this study with data collection tools such as interviews, observations and documentation studies. The results of the study are: (1) The policies taken by the principal and teachers both have a desire to improve the quality of school education through the application of community-based learning models, but there is no collaboration. (2) Programs to improve the quality of school education by implementing community-based learning models do not exist, but school principals and teachers do. (3) The strategy to improve the quality of school education lies in the application of strict discipline, so that all teachers are disciplined to teach. The absorption of the subject matter is achieved. (4) Supporting factors in improving the quality of school education, the existence of a high level of teacher professionalism and the application of strict discipline. Making teachers teaching students can be carried out properly, the quality of the learning process is created which indicates the graduation standard is obtained a maximum of one hundred percent.